2011
DOI: 10.2174/187152811795564109
|View full text |Cite
|
Sign up to set email alerts
|

Skin Prick Test with Self-Saliva in Patients with Oral Aphthoses: A New Diagnostic Pathergy for Behcets Disease and Recurrent Aphthosis

Abstract: There may be some difficulties to differentiate Behcet’s disease (BD), recurrent aphthosis (RA), and herpetic aphthous ulceration, from other mimicking oral disorders. Despite of unexpected sensitivity and responsiveness, the skin pathergy test regarding a non-specific hypersensitivity has long been thought as one of auxiliary diagnostic benefits for BD.To determine the potential usefulness and disease specificity of the prick reaction with saliva, a skin prick test with neat and filter-sterilized saliva was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The more important reason seems to be the widespread use of disposable needles instead of blunt, reusable, sterilized needles. Recently Togashi et al 19 have proposed a new diagnostic pathergy test to overcome this problem. They performed a skin prick test with neat and filter-sterilized saliva on the forearm skin.…”
mentioning
confidence: 99%
“…The more important reason seems to be the widespread use of disposable needles instead of blunt, reusable, sterilized needles. Recently Togashi et al 19 have proposed a new diagnostic pathergy test to overcome this problem. They performed a skin prick test with neat and filter-sterilized saliva on the forearm skin.…”
mentioning
confidence: 99%
“…Interestingly, pricking with filter‐sterilized saliva failed to produce a positive skin reaction when neat saliva was used. Furthermore, microbial culture of saliva from patients with Behcet's disease revealed numerous streptococcal colonies ; these findings suggest that a skin‐prick test using self‐saliva can be a simple and valuable in vivo diagnostic approach for differentiating Behcet's disease from other oral diseases. These findings warrant further evaluation in large‐scale studies.…”
Section: Salivary Changes In Systemic Diseases With Possible Oral Mucmentioning
confidence: 90%
“…Pathergy is a reaction seen in some patients with Behcet's disease to a sterile needle prick . A skin‐prick test with the patient's own saliva has been recently described to be of diagnostic importance in patients with Behcet's disease: 90% of patients with Behcet's disease exhibited an indurated erythema at the skin site pricked with their own saliva . Interestingly, pricking with filter‐sterilized saliva failed to produce a positive skin reaction when neat saliva was used.…”
Section: Salivary Changes In Systemic Diseases With Possible Oral Mucmentioning
confidence: 99%
“…This information suggests that the positive reaction might be a cutaneous response to some bacteria living on the surface of the skin. In a recent study, performed by Togashi et al suggested that a new diagnostic pathergy test may solve the methodological problems [62]. They performed a skin prick test with ilter-sterilized saliva on forearm skin.…”
Section: Pathergy Reactionmentioning
confidence: 99%
“…Of the patients with BD, 90% showed indurative erythema at the skin site pricked with self-saliva, and 60% of recurrent aphthous stomatitis patients showed weak reaction. They suggested that skin prick test using self-saliva can be a diagnostic test for differentiating BD from other mucocutaneous diseases [62].…”
Section: Pathergy Reactionmentioning
confidence: 99%